Estimates of Heritabilities and Genetic Correlations for Growth and Gonad Traits in Blunt Snout Bream, Megalobrama amblycephala. Issue 1 (February 2016) - Zhao, Honghao; Zeng, Cong; Wan, Shiming; Dong, Zaijie; Gao, Zexia
Abstract: Blunt snout bream, Megalobrama amblycephala, is an herbivorous freshwater fish and has been recognized as a main aquaculture species in the Chinese freshwater polyculture system. The objective of the study is to estimate the genetic parameters for growth, body shape, and gonad traits for M. amblycephala at 1 yr of age. The phenotypic analysis showed that coefficients of variation for gonad traits had large variation relative to the other traits analyzed, and there was no sexual dimorphism by comparing growth and body shape in M. amblycephala . Based on restricted maximum likelihood and Markov chain Monte Carlo Bayesian methods using the animal model, the heritabilities of body weight (0.423–0.504), body length (0.309–0.678), body height (0.408–0.599), and dressed weight (0.359–0.643) were moderate and high, while the other traits, including conditional factor (0.029–0.199), body shape coefficient (0.095–0.405), edible ratio (0.073–0.207), gonad weight (0.018–0.170), and gonadosomatic index (0.050–0.222), had moderate or low heritabilities. High genetic and phenotypic correlations were found among growth traits, but not between growth traits and body shape or gonad traits except dressed weight. Based on our results, it could be efficient to combine the selection on body weight for fast growth and nonearly sexual maturity varieties of M. amblycephala breeding.